The Emerging Functions of Long Noncoding RNA in Immune Cells: Autoimmune Diseases - Keshav Raj Sigdel; Ao Cheng; Yin Wang; Lihua Duan; YanLin Zhang (Journal of Immunology Research)
The long noncoding RNAs (lncRNAs) are RNA transcripts more than 200 nucleotides in length, which do not encode proteins. The lncRNAs are emerging as an important regulator of biological process, such as chromatin remodeling, gene transcription, protein transport, and trafficking through diverse mechanisms. The lncRNAs play crucial role in various multigenetics human diseases including cancers and neurological diseases and currently its role in autoimmune diseases is attracting many researchers. Recent studies have reported that differentiation and activation of immune cells, T cells, B cells, macrophages, and NK cells have correlation with lncRNAs, which have also an essential role in autoimmune diseases such as rheumatoid arthritis and SLE. Therefore, elucidation of the roles of lncRNAs in autoimmunity could be beneficial to understand the pathogenesis of autoimmune diseases. In this review article we attempt to highlight the recent progress regarding lncRNAs studies and summarize its role in autoimmune diseases.